An Interpersonal Perspective on HR Attributions: Examining the Role of Line Managers, Coworkers, and Similarity in Work-Related Motivations - Beijer, Susanne; Van De Voorde, Karina; Tims, Maria (Frontiers in Psychology, 2019)
Given that various studies have linked Human Resource (HR) attributions to important individual and organizational outcomes, the question that arises is what causes these HR attributions. By taking an interpersonal perspective it is examined how employees both individually as well as collectively interpret HR practices. Based on social information processing theory this study among 87 line manager-employee-coworker triads shows that line managers affect HR attributions of employees, and that employees also mutually influence each other’s HR attributions. This mutual influence process between coworkers is strengthened by similarity in work-related motivations. Our findings support the proposition that employees’ social environment at work, particularly their line manager and coworker, matters in HR attribution processes. This stresses the importance of considering the social environment at work to more fully understand the factors that shape employees’ understandings of HR practices.